AB0339 THE IMPORTANCE OF THERAPEUTIC COMPLIANCE: ADHERENCE TO METHOTREXATE AND ITS ROLE IN IMMUNOGENICITY. (2nd June 2020) - García, P.; González Fernández, M.; Rivas, M. N.; Duruelo, J.; Garmendia, E.; Arostegui Lavilla, J.; Perez-Ruiz, F.; Alonso, A.; Modesto, C.; Blanco Cáceres, B. A.
Abstract : Background: Immunogenicity against adalimumab leads to loss of response and secondary failure to biologic therapy; however, concomitant use of methotrexate (MTX) seems to reduce the development of anti-drug antibodies (ADAbs) in a dose-dependent manner. Suboptimal adherence to MTX may favour ADAbs appearance. Objectives: To evaluate the relationship between MTX adherence and ADAbs development. Methods: Observational study among adult patients with chronic inflammatory arthropathy, followed in a tertiary care centre, who were in treatment with MTX and adalimumab. ADAbs formation in relation to MTX adherence was assessed. Results: 33 patients were included, with a MTX adherence overall mean of 82.13 (12.45%-100%, median adherence 92.19%). Only 9.09% (n=3) of the patients developed ADAbs, being its MTX adherence mean of 60.95% (46.47%-70%, median adherence 66.39%); ADAbs negative group showed an average MTX adherence of 84.23% (12.45%-100%, median adherence 94.29%). A statistically significant result (p<0.05) between groups was found. No statistically significant differences (p>0.05) involving MTX adherence and its dose were found. Conclusion: While the sample is small, this study suggests that ADAbs development may be influenced by MTX adherence, thereby promoting adequate MTX adherence should be a priority in the daily practice of every rheumatologist. References: [1]World Health Organization. Adherence to long term therapies: evidence for action. 2003. [2]Krieckaert CL, Nurmohamed MT, Wolbink GJ. Methotrexate reduces immunogenicity in adalimumab treated rheumatoid arthritis patients in a dose dependent manner. Annals of the Rheumatic Diseases. 2012;71:1914-1915. [3]Zhang J, Xie F, Delzell E, et al. Impact of biologic agents with and without concomitant methotrexate and at reduced doses in older rheumatoid arthritis patients. Arthritis Care Res (Hoboken). 2015;67(5):624–632. doi:10.1002/acr.22510 [4]Jani M, Barton A, Warren RB, Griffiths CE, Chinoy H. The role of DMARDs in reducing the immunogenicity of TNF inhibitors in chronic inflammatory diseases. Rheumatology (Oxford). 2014;53(2):213–222. doi:10.1093/rheumatology/ket260. Disclosure of Interests: Paula García: None declared, Marta González Fernández: None declared, Mayra Nathali Rivas: None declared, Javier Duruelo: None declared, Elena Garmendia: None declared, Javier Arostegui Lavilla: None declared, Fernando Perez-Ruiz Consultant of: Amgen Lilly, Speakers bureau: Amgen, Alberto Alonso: None declared, Consuelo Modesto: None declared, Boris Anthony Blanco Cáceres: None declared